Spontaneous preterm labor is associated with an increase in the proinflammatory signal transducer TLR4 receptor on maternal blood monocytes - Sashti Nupur A; Pratap Siddharth; Izban Michael G; Nowicki Bogdan J; Pawelczyk Edyta; Sanderson Maureen; Nowicki Stella (BMC, 2010)
Abstract Background Localized inflammation and increased expression of TLR4 receptors within the uterus has been implicated in the pathogenesis of preterm labor. It remains unclear whether intrauterine inflammatory responses activate the maternal peripheral circulatory system. Therefore we determined whether increased TLR4 expression is present in the peripheral maternal white blood cells of women with spontaneous preterm labor. Methods This is a cross-sectional study of 41 preterm labor cases and 41 non-preterm controls. For each case and control sample, RNA was purified from white blood cells and TLR4 mRNA pool size was evaluated by quantitative PCR. Protein expression levels were determined by flow cytometry. Statistical evaluation using multiple linear regressions was used to determine any significant differences between the cases and controls. The purpose was to determine association prevalence of TLR4 levels and preterm labor. Results Adjusted mean TLR4 mRNA levels of 0.788 ± 0.037 (standard error) for preterm labor and 0.348 ± 0.038 for the corresponding pregnant control women were statistically significantly different (P = 0.002). Using the lower 95% confidence interval of the mean expression level in PTL subjects (0.7) as a cutoff value for elevated TLR4 mRNA levels, 25/41 (60.9%) of PTL patients expressed elevated TLR4 mRNA as compared to 0/41 (0%) in control subjects. The TLR4 receptor levels in the granulocyte fraction of white blood cells from preterm labor and pregnant controls were similar. However, TLR4+/CD14+monocytes were 2.3 times more frequent (70% vs. 30%) and TLR4 also had a 2.6-fold higher density (750 vs. 280 molecules per cell) in preterm labor women compared with pregnant controls. There was no difference in the levels of TLR4 in patients at term. Conclusions Patients with preterm labor exhibited elevated levels of CD14+ maternal blood monocytes each bearing enhanced expression of TLR4, indicating that the peripheral circulatory system is activated in patients with preterm labor. Elevated leukocyte TLR4 levels may be a useful biomarker associated with preterm labor.